Intra-Family Economic and patrimonial violence against women - Córdova López, Ocner (2017)
In this article we analyze the new type of violence against women and other family members, i.e. intra-family economic and patrimonial violence, which has recently been regulated by Law No. 30364 - Law to prevent, punish, and eradicate violence against women and other family members. The paper analyzes the definition of the concept, its characteristics, the importance of preventing, punishing, and eradicating this type of violence, the way it has been regulated in other neighboring countries, the different assumptions and typical cases of economic and patrimonial violence, their differences, and the importance of eradicating this type of violence in the family.